Zakah as tool for social cause marketing and corporate charity: a conceptual study. Issue 1 (4th March 2019) - Abdullahi, Shafiu Ibrahim
Abstract : Purpose: This paper explores the role of Zakah in social cause marketing. Academic literature on Islamic economics, finance and management mostly deals with the links that exists between Zakah and consumption, neglecting important and strategic links with social cause marketing. This paper emanated from need to outline social cause and the charitable role of Zakah in promoting Halal businesses, poverty alleviation and sustainable development. Most works in the field of Zakah did not foresee the role of marketing. This is a misjudgement, as this work showed that Zakah yields large and measurable social gains to help the society and a firm. Design/methodology/approach: Secondary sources were used in writing this paper. Available literature in the form of journals, books, manuals and reports was referred to. As a conceptual work, the paper does not test hypothesis or pretends to provide empirical evidences. It uses mathematical economics in arriving at some of the conclusions. Findings were derived through deductions and critical discourses, not through crunching of primary data. Findings: The paper shows how Zakah, Halal consumption and corporate social responsibility are connected and highlights the role of Zakah as a social marketing tool. It shows how Zakah affects consumption through marginal propensity of Zakah recipients who spend Zakah money on basic needs. Research limitations/implications: The paper looks at the broad aspects of Zakah and social marketing. How to make Zakah a pillar of Islamic firms' social cause programs shall be the focus of future academic works in this area. Originality/value: The paper is unique in drawing attention of Islamic firms to the effectiveness of Zakah in building a corporate image. It draws the attention of firms, activists, academics and governments to functions of Zakah that have not been studied in depth.